(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
An Empirical Analysis has been conducted to compare and contrast the returns of Gold Commodity with the silver commodity during the Diwali Festival. Gold Mini and Silver Mini have been considered as a base and data pertaining to 10 years from 2010 to 2019 have been extracted from Multi Commodity Exchange. Statistical tools have been employed like Karl Pearson coefficient correlation, the test of significance of correlation, percentile, and trends have been utilized to evaluate the impact of the Diwali festival. The study concludes that Gold commodity and Silver commodity have a linear positive relationship corresponding with the Diwali festival. Considering returns the Gold commodity is a notch ahead and offers better returns than the silver commodities. Hence investors should capitalize on this opportunity present in Multi commodity exchange.